KEPUASAN KERJA KARYAWAN ERAFONE CABANG BANTAR GEBANG DI PENGARUHI OLEH KEPEMIMPINAN MELALUI MOTIVASI SEBAGAI VARIABEL INTERVENING - Edy Sanusi Silitonga; Rachmad Setiawan (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2024)
Purpose to determine the influence of leadership on employee job satisfaction at Erafone Bantar Gebang Branch through motivation. This research uses quantitative methods. The population in this study were employees of Erafone Bantar Gebang Branch. The technique used for sampling is a saturated sample, all members of the population are sampled, because the population is relatively small. The data analysis method uses path analysis. The research results can be concluded as follows: 1). Leadership directly has a significant effect on employee job satisfaction. 2). Motivation directly has a significant effect on employee job satisfaction. 3). Leadership directly has a significant effect on motivation. 4). Indirectly, leadership has no effect on job satisfaction of Erafone Bantar Gebang Branch employees through motivation